FAKTOR-FAKTOR YANG MEMENGARUHI RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE 2016-2024 - FIONI FIONI; ERIKA JIMENA ARILYN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the effect of the current ratio (CR), debt to equity ratio (DER), net profit margin (NPM), price to earnings ratio (PER), and return on equity (ROE) on stock returns. The population of the study consists of companies in the Food and Beverages subsector during the period 2016–2024. The sample was obtained using a purposive sampling method, resulting in a total of 90 samples from 10 companies over a 9-year period. Secondary data were obtained from the official website of the Indonesia Stock Exchange (IDX) and analyzed using multiple regression with the help of the E- Views 12 application. The results of the study indicate that the return on equity (ROE) has a significant effect on stock returns. Meanwhile, the current ratio (CR), debt to equity ratio (DER), net profit margin (NPM), and price to earnings ratio (PER) do not have a significant effect on stock returns.